2017
DOI: 10.1038/jhg.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

A common deletion in the haptoglobin gene associated with blood cholesterol levels among Chinese women

Abstract: Haptoglobin (HP) protein plays a critical role in binding and removing free hemoglobin from blood. A deletion in the HP gene affects the protein structure and function. A recent study developed a novel method to impute this variant and discovered significant association of this variant with low-density lipoprotein (LDL) and total cholesterol levels among European descendants. In the present study, we investigated this variant among 3,608 Chinese women. Consistent with findings from Europeans, we found signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Although rs7200153 had a slightly higher PPSNP, rs5471 is likely to be the true causal variant given its proximity to the HP promoter, stronger effect of HP expression, and experimental data demonstrating decreased transcriptional activity for rs5471-C in West African populations [25][26][27] . Prior studies have identified HP as having an effect on cholesterol and the association of rs5471 is well supported by multi-ancestry genetic association studies 19,28,29 .…”
Section: Assessment Of Ancestry-specific Eqtlsmentioning
confidence: 83%
“…Although rs7200153 had a slightly higher PPSNP, rs5471 is likely to be the true causal variant given its proximity to the HP promoter, stronger effect of HP expression, and experimental data demonstrating decreased transcriptional activity for rs5471-C in West African populations [25][26][27] . Prior studies have identified HP as having an effect on cholesterol and the association of rs5471 is well supported by multi-ancestry genetic association studies 19,28,29 .…”
Section: Assessment Of Ancestry-specific Eqtlsmentioning
confidence: 83%
“…It is speculated that rs5471 A, rs5472 A, HP 1 , and rs2000999 G alleles and the A-1-G haplotype were prevalent, and HP 2 and G-1-G haplotypes (this means HP 1F and mainly migrations from Europe and Africa) were rare in Native Americans. Interestingly, all of the alleles with higher frequency in the Latin Americans are associated with higher serum HP and lower cholesterol levels 5,23,24,[27][28][29][30] . In addition, the genetic influx from populations of other continents into Peruvians seems to be relatively lower than into other Latin Americans, as suggested by previous studies on autosomal, X-, or Y-chromosomal and mitochondrial markers or SNPs or our FUT2 data on the same subjects [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, associations between these polymorphisms as well as rs2000999 and serum cholesterol levels were reported 5,23,24,[27][28][29][30] . Each allele of the polymorphisms that correlated with a higher HP level was associated with lower cholesterol levels despite the population, although no report is available for rs5471 yet.…”
Section: Several Genetic Polymorphisms Of the Haptoglobin Gene (Hp) Omentioning
confidence: 99%
“…Elevated LDL cholesterol is a risk factor for AMI [27] and several lines of evidence have shown that Hp 2 allele and single nucleotide polymorphism (SNP) rs2000999, located within 15 kb of HP gene are associated with elevated levels of total cholesterol and LDL cholesterol in European [14, 4144] and in East Asians, including Singapore Chinese population [19, 45], and are suggested to act via different pathways in modulating total cholesterol and LDL cholesterol level [42, 45]. Boettger et al proposed that higher LDL levels in Hp 2-2 phenotype could be attributed to less efficient binding capacity of Hp 2-2 haptoglobin form to APOE, impairing the clearance of LDL cholesterol [32, 42].…”
Section: Discussionmentioning
confidence: 99%